Governing by Network : The New Shape of the Public Sector - Goldsmith, Stephen, 1946- (Book collections on Project MUSE., 2004)
Examines for the first time the US government's transformation from centralized control over public programmes to facilitating services through networks of nongovernmental entities, as seen through the experience of dozens of public innovators.